2010
DOI: 10.1007/s10865-010-9280-x
|View full text |Cite
|
Sign up to set email alerts
|

Mood and transient cardiac dysfunction in everyday life

Abstract: Emotion in daily life may be associated with transient myocardial ischemia, ventricular tachycardia and impaired autonomic function in cardiac patients, but the precise temporal sequence is unclear. Eighty-eight patients with suspected coronary artery disease underwent 24-h electrocardiographic monitoring, and affect was measured with the Day Reconstruction Method. Thirteen patients (15%) experienced one or more episodes of ST depression or ventricular tachycardia, nine of whom provided concurrent mood data. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Bhattacharyya & Steptoe (2011) Monitored coronary artery disease patients over time and found that negative moods preceded cardiac dysfunction in the 15 minutes before the episode. Blascovich & Tomaka (1996) Reviewed evidence showing that stress raises heart rate and blood pressure, where a challenge does not because arterial dilation counteracts the effects of increased heart rate.…”
Section: Yanek Et Al (2013)mentioning
confidence: 99%
“…Bhattacharyya & Steptoe (2011) Monitored coronary artery disease patients over time and found that negative moods preceded cardiac dysfunction in the 15 minutes before the episode. Blascovich & Tomaka (1996) Reviewed evidence showing that stress raises heart rate and blood pressure, where a challenge does not because arterial dilation counteracts the effects of increased heart rate.…”
Section: Yanek Et Al (2013)mentioning
confidence: 99%
“…Depression is a risk factor for poor health outcomes in patients with cardiovascular disease and this study identified a simple method to reduce this potential risk factor. 7,8 Pain was measured in three of the relaxation studies only. 32,35,38 All of these studies used visual analogue scales with no significant effects for music or massage on pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…7 Anxiety, a common psychological response (60%) in patients with cardiovascular disease, can cause unwanted clinical responses such as arrhythmias and ischemia that can lead to poor cardiovascular patient outcomes during cardiac catheterization. 8,9 In addition, depression is a common symptom (20%) in patients with cardiovascular disease. 10,11 It is important to understand whether non-pharmacological interventions to reduce psychological distress are effective in people as they undergoing diagnostic cardiac catheterization.…”
mentioning
confidence: 99%
“…There is no consensus about the definition of psychological distress, but for the purpose of this review, the focus is on anxiety and depression as markers of emotional status [14]. Anxiety, a common psychological response (60%) in patients with cardiovascular disease, can cause unwanted clinical responses such as arrhythmias and ischemia that can lead to poor cardiovascular patient outcomes during cardiac catheterization [15,16]. In addition, depression is a common symptom (20%) in patients with cardiovascular disease [17,18].…”
Section: Introductionmentioning
confidence: 99%